Perfil tecnológico e funcional de cepas probióticas em leite fermentado - Casarotti, Sabrina Neves [UNESP] (2013)
During storage of fermented milk, probiotic bacteria must retain their viability in order to promote health benefits to the consumer. The composition of the culture used during fermentation and the ingredients added to milk can influence the viability of probiotics during refrigerated storage. Furthermore, it is important that probiotics survive to the harsh conditions during the passage through the gastrointestinal tract (GIT). The presence of different drugs in the GIT can also suppress or reduce the therapeutic effect of probiotic microorganisms. The main objective of this study was to evaluate the effect of the composition of the culture and different matrices on the quality of fermented milk and the effect of medications on the survival of commercial probiotics strains. The work was divided in four parts for better distribution and execution of experiments. In the first part, it was studied the effect of the composition of culture during fermentation through the production of organic acids, lactose consumption and kinetics of acidification and during storage, evaluating the pH, syneresis, viability of microorganisms (S. thermophilus , Lactobacillus acidophilus and Bifidobacterium animalis subsp.), survival of probiotics against simulated GIT conditions, sensory characteristics and concentration of the organic acids. The bacteria that produced the largest amount of lactic acid were the homofermentatives S. thermophilus and L. acidophilus. Fermented products containing B. animalis subsp. lactis showed the highest levels of acetic acid at the end of fermentation. Only L. acidophilus was able to metabolize citrate, while the levels of pyruvate rose slightly during fermentation. The kinetics of acidification was influenced by the composition of lactic acid culture. The higher pH values at the end of storage were obtained for treatments with probiotic cultures. The syneresis reduced during storage and the lowest value was observed in the ...